Biopolymers Lignin, Proteins, Bioactive Nanocomposites - Abe, Akihiro; Dusek, Karel; Kobayashi, Shiro; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Table of Contents Lignin Structure, Properties, and Applications Hyoe Hatakeyama and Tatsuko Hatakeyama Tensile Mechanics of ga(B-Helical Coil Springs Atsushi Ikai Bioactive Polymer/Hydroxyapatite (Nano)composites for Bone Tissue Regeneration Kinga Pielichowska and Stanislaw Blazewiczs
Lignin Structure, Properties, and Applications -- Tensile Mechanics of ?-Helical Coil Springs -- Bioactive Polymer/Hydroxyapatite (Nano)composites for Bone Tissue Regeneration.
Keywords: Chemistry; Polymers; Biochemistry; Biomaterials; Nanotechnology; Chemistry; Polymer Sciences; Biomaterials; Protein Science; Nanotechnology